THE VALUES OF RELIGIOUS MODERATION IN RELIGIOUS LEARNING IN THE MASTER OF ISLAMIC EDUCATION MANAGEMENT - Hafid, Erwin; Muzakkir, Muzakkir (Idaarah: Jurnal Manajemen Pendidikan, 2025)
This study examines the value of religious moderation in the Islamic Education Master Program (MPI) UIN Alauddin Makassar. The main objective is to find out the general picture of the value of religious moderation among the academic community of the MPI study program, to find out the implementation of the concept in education and learning, and the practical implications of the application of the value of religious moderation for the academic community of MPI. Through interviews with several sources, it can be seen, that there is a deep understanding of the essence of religious moderation adopted by lecturers and students, namely being religious without being extreme, tawassuth, and having a tolerant and friendly attitude towards differences. With the integration of teaching methods, significant changes are seen in the interaction between students and lecturers. Even so, there are still obstacles faced in its implementation. As a recommendation, this study suggests the need for regular training for lecturers and students and optimization of social media as a means of promotion and education to strengthen the value of religious moderation among the academic community.